Pemanfaatan Metode Pembayaran QRIS bagi Kalangan Muda sebagai Upaya Mempermudah Transaksi Keuangan - Ulfatul Khasanah; Ayu Maretta Maharani (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
Continuous improvements in infrastructure, security measures, and user education can help address these weaknesses and improve the overall effectiveness of QRIS as a digital payment solution. Some of the roles of using QRIS in the millennial generation are convenience. QRIS makes it easy for millennials to make digital payments without the need to carry cash or credit/debit cards. They can simply use their mobile phones to scan the QR code and complete the payment transaction. QRIS transactions are processed in real-time, meaning payments can be completed almost instantly. Many digital payment platforms that support QRIS offer promotions and discounts to users who make payments using their platform. This is especially attractive to millennials who are always looking for ways to save money.